Romantic Perfectionism and Perceived Conflict Mediate the Link between Insecure Romantic Attachment and Intimate Partner Violence in Undergraduate Students - Lafontaine, Marie-France (Journal of family violence, 2021)
This study examined whether romantic attachment insecurity (i.e., anxiety and avoidance) was indirectly related to intimate partner violence (IPV) victimization through two types of romantic perfectionism (i.e., self-oriented and socially prescribed) and perceived couple conflict. University students (N = 564; 422 women) between 17 and 25 years of age, who were involved in a romantic relationship, completed online questionnaires. Romantic attachment insecurity was positively associated with physical and psychological IPV victimization. Serial mediation models revealed significant indirect effects of attachment insecurity on IPV victimization through (a) socially prescribed (but not self-oriented) romantic perfectionism and (b) perceived couple conflict. Specifically, higher levels of attachment anxiety and attachment avoidance were indirectly associated with more IPV victimization (i.e., physical and psychological) through higher levels of socially prescribed romantic perfectionism and perceived couple conflict. This study highlights a viable mechanism underlying the link between romantic attachment insecurity and IPV victimization. Future research directions are discussed.